The Pengaruh Content Marketing Terhadap Keputusan Pembelian Produk Fashion UMKM Kisa Gallery - Donni Juni Priansa; Dinda Annisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The company's marketing strategy now incorporates social media, particularly for content marketing. This study investigates the impact of content marketing strategies on millennials' fashion purchasing decisions. Through an online survey, a quantitative approach was utilised in this investigation. This study's participants are customers of UMKM Kisa Gallery at Bandung. The data analysis method employs basic linear regression. This study determined that the effect of marketing content on fashion purchasing decisions was 0.646, and the R Square value was 0.411, indicating a classification of strong influence. This research implies that UMKM Kisa Gallery must improve marketing content through interesting, informative, and relevant content. UMKM Kisa Gallery must also design a more comprehensive and effective marketing strategy considering other factors influencing purchasing decisions.